Assessment of the Global and Regional Circumferential Strain of Abdominal Aortic Aneurysm with Different Size by Speckle‐Tracking Echocardiography. (8th February 2021) - Li, Tan; Liu, Xiaozheng; Sun, Haiyang; Ning, Hongxia; Yang, Jun; Ma, Chunyan
Abstract : Objectives: We aimed to use speckle‐tracking echocardiography (STE) to quantify circumferential aortic strain of abdominal aortic aneurysms (AAA) with different size. Methods: A total of 87 AAA patients were included. The morphological variables, including aortic maximum diameter (MD), end systolic area (ESA), end diastolic area (EDA), and thickness and area of intraluminal thrombus (ILT), were measured by ultrasound. STE was applied to calculate circumferential strain (CS) at 6 equally divided segments of the aorta at MD. We evaluated the mean value of peak strain along the 6 segments as global circumferential strain (GCS). Results: Large AAA (≥5.5 cm) patients had higher MD, ESA, EDA, AAA length, ILT thickness, and area, but lower fractional area change, GCS, and segmental CSs than small AAA (<5.5 cm) subjects (all P < .05). Compared with AAA <4.5 cm group, AAA patients ≥4.5 cm possessed increased MD, ESA, EDA, AAA length, ILT thickness, and area, which results were also reflected in the comparison between AAA <6.5 and ≥6.5 cm group. In small AAA patients, GCS and regional strains in CS1, CS3, and CS5 segments were lower in AAA subjects ≥4.5 cm than those <4.5 cm (all P <.05). However, no significant differences in the GCS and regional CS between ≥6.5 and <6.5 cm group were found. Correlation analysis revealed a significant negative association of GCS with MD, ESA, and EDA, even after adjusting the potential confounding factors (all P < .05). Conclusions: Our findings may yield insight into the structural strain characteristics of AAA wall with different size, which adds the benefit of using simple echocardiography‐derived biomechanics to stratify AAA patients.